Discrete resource allocation problems and military applications - Tiešis, Vytautas (Lietuvos matematikos rinkinys, 2002)
The paper deals with the discrete resource allocation problem and its application in the attack steering systems. The non-linear models of multiple target prioritisation are presented in the case of multiple different weapons. The fast greedy algorithms are presented and investigated. In the case of homogeneous resources (weapons) the algorithms give optimal solutions. The experiments show that the algorithms give sufficiently exact solutions in the case of different weapons.